Variable Regions of PI4P 5-Kinases Direct PtdIns(4,5)P2 Toward Alternative Regulatory Functions in Tobacco Pollen Tubes - Stenzel, Irene; Ischebeck, Till; Quint, Marcel; Heilmann, Ingo (Frontiers in Plant Science, 2012)
The apical plasma membrane of pollen tubes contains different PI4P 5-kinases that all produce phosphatidylinositol-4,5-bisphosphate (PtdIns(4,5)P2) but exert distinct cellular effects. In the present example, overexpression of Arabidopsis AtPIP5K5 or tobacco NtPIP5K6-1 caused growth defects previously attributed to increased pectin secretion. In contrast, overexpression of Arabidopsis AtPIP5K2 caused apical tip swelling implicated in altering actin fine structure in the pollen tube apex. AtPIP5K5, NtPIP5K6-1 and AtPIP5K2 share identical domain structures. Domains required for correct membrane association of the enzymes were identified by systematic deletion of N-terminal domains and subsequent expression of fluorescence-tagged enzyme truncations in tobacco pollen tubes. A variable linker region (Lin) contained in all PI4P 5-kinase isoforms of subfamily B, but not conserved in sequence, was recognized to be necessary for correct subcellular localization of AtPIP5K5, NtPIP5K6-1 and AtPIP5K2. Deletion of N-terminal domains including the Lin domain did not impair catalytic activity of recombinant AtPIP5K5, NtPIP5K6-1 or AtPIP5K2 in vitro; however, the presence of the Lin domain was necessary for in vivo effects on pollen tube growth upon overexpression of truncated enzymes. Overexpression of catalytically inactive variants of AtPIP5K5, NtPIP5K6-1 or AtPIP5K2 did not influence pollen tube growth, indicating that PtdIns(4,5)P2 production rather than structural properties of PI4P 5-kinases was relevant for the manifestation of growth phenotypes. When Lin domains were swapped between NtPIP5K6-1 and AtPIP5K2 and the chimaeric enzymes overexpressed in pollen tubes, the chimaeras reciprocally gained the capabilities to invoke tip swelling or secretion phenotypes, respectively. The data indicate that the Lin domain directed the enzymes into different regulatory contexts, possibly contributing to channeling of PtdIns(4,5)P2 at the interface of secretion and actin cytoskeleton.